Mobile Collection and Dissemination of Seniors’ Skills - Salamin, Anne-Dominique; Xia, Leyun (International Journal of Advanced Corporate Learning (iJAC), 2015)
By 2050, the 60+ population will have reached 2 billion—this will be the first time in history when people aged over 60 will outnumber children aged 14 and under. The Mocodis project focused on collecting and valorizing seniors’ competencies in the firm, which can, as such, be regarded as a group producing value and no longer perceived as a vulnerable group deserving special attention. We focused on “senior” in the sense of “elder workers, integrated in a company or association, and retiring in less than 5 years”. The MOCODIS system aims at collecting resources, such as video, audio and text, on a voluntary basis, illustrating a competency a senior believes he holds and which he wishes to transmit to a junior in the firm. Then, the system organizes and analyses data and generates on the fly microcapsules of courses combined in such a way as to produce units containing independent knowledge. Each capsule lasts about 5 minutes and consists in a smart mix of video, audio and text resources. This enables a junior to launch a research on a specific notion and consume the course capsule when and where it most suits him, on a mobile or desktop support. After consumption, he assesses each learning resource on different criteria (usefulness, interest, difficulty etc.). The next time Mocodis identifies a similar request, it will prioritize the resources included in the next capsule, according to their best evaluation. The MOCODIS-TS platform was developed by the University of Applied Sciences Western Switzerland (HES-SO) and can be used for any in-house training in the enterprise environment. We will perform a demonstration of the application, provide scenarii on how to use the system and present feedback from the organizations that wish to use MOCODIS in-house.